1917 Or. Gen. and Special Laws 805, ch. 377, § 5 - (:unkn) unknown (My University, 1917)
Every person in the business of selling, leasing or otherwise transferring a pistol, revolver, or other firearm of a size which may be concealed upon the person, whether such seller is a retail dealer, pawnbroker or otherwise, shall obtain a legal register (as per Section 6) from the State Printer, at a cost of $3.00 per 100 leaves in duplicate, in which shall be entered at the time of sale the date of sale, name of maker, number (if any), caliber, name of purchaser, permanent resident, temporary residence, age, occupation, height, color of skin, color of eyes, color of hair and signature of purchaser. (The purchaser is required to sign his name in the aforesaid register in the space provided for the same.) Any person signing a fictitious name or address shall be guilty of a misdemeanor. Any person who shall fail to keep a register and to enter therein the facts required by this section shall be guilty of a misdemeanor. Such register shall be open at all reasonable hours for the inspection of any peace officer. This section shall not apply to wholesale dealers in their business intercourse with the retail dealer, nor to the wholesale or retail dealer in the regular or ordinary transportation of firearms as a merchandise by mail, express, or other mode of shipment, to points outside of the city, town, or municipal corporation wherein they are situated. Any person who violates the provisions of this section is guilty of a misdemeanor, and upon conviction thereof shall pay a fine of not less than $100.00 nor more than $500.00 or shall be imprisoned in the county jail or reformatory for not less than thirty days nor for more than one year, or be punished by both fine and imprisonment.
Keywords: REGISTRATION